DESTINATION BRANDING DESA WISATA KAMPUNG TEMPE DESA BEJI - BATU - Agustinus Klaudius; Asfira Rachmad Rinata; Muhammad Abdul Ghofur (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2022)
Beji Village, Junrejo District is one of the second tempe tourism centers after Sanan in Malang City. Besides having the potential of an educational tourism village, the kampung tempe of Beji village also empowers the community's home industry in making tempe. The analysis used in this research is descriptive qualitative using the concept of place branding. The results of this study indicate that the destination branding of Tempe village, Beji Village as an educational tourism village, can be reviewed with the concept of place brand image, place brand personality and place brand identity. The place brand image that can be seen is in the uniqueness of the attraction that is offered as a tourist village of Kampung Tempe, which is not only selling souvenirs and processed tempe products but also educational activities about tempe to visiting tourists. Place brand perconality can be seen in various other supporting activities such as the Beji Kampung Tempe festival which integrates with the local government in its promotion. Place brand identity can be seen in the naming of the tourist village, the logo and the Beji Berkreasi tagline which is depicted in every corner of the tourist village. The factors that support the community to participate in the development of the tempe village educational tourism village are due to good communication between the government and the community and the productive age. Place Branding can show the greatest value that comes from uniqueness and has a strong relationship that can affect a person's perception of being able to remember something that is seen and felt.